(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Objective To study the medicinal utility of cadamba fruit, in reducing the toxic effects of arsenic on the liver in Swiss albino mice and the importance of cadamba fruit for the people as a tonic in reducing the effect of arsenic by giving simultaneously both cadamba ,arsenic to the albino mice.Method Oxidative stress was induced by oral administration 4 mgkg b. wt of arsenic trioxide (As2O3,) for 45 days in experimental rats. The level of liver arsenic concentration, lipid peroxidation, reduced glutathione (GSH), catalase (CAT), superoxide dismutase (SOD), glutathione reductase (GR), glutathione-S-transferase (GST), and glutathione peroxidase (GPx) were determined in adult male Wistar rats. Hepatotoxicity was assessed by quantifying the aspa alanine transaminase (ALT) and alkaline phophatase (ALP). Hepatoprotective efficacy of cadamba fruit extract (100 mgkg b.wt) was evaluated by combination treatment with As2O3. Results As2O3 administration leads to the generation of reactive oxygen species (ROS), arsenic accumulation, serum marker enzymes release and decrease in antioxidant enzymes in liver. Retention of arsenic in liver caused increased level of lipid per oxidation with a concomitant decline in the glutathione dependant antioxidant enzymes and antiperoxidative enzymes. Cadamba fruit extract treatment protected the liver from arsenic induced deterioration of antioxidant levels as well as oxidative stress. And also a significant decrease in hepatic arsenic accumulation and serum marker enzymes was observed. Histopathological examination revealed a curative improvement in liver tissue.Conclusions These findings lead to the conclusion that cadamba fruit extract may have the potential to protect the liver from arsenic induced toxic effects.